The influence of electronic service quality and electronic word of mouth (eWOM) toward repurchase intention (study on e-commerce in Indonesia) - Rachbini, Widarto; Diana Anggraeni; Wulanjani, Harimurti (Penerbit Universiti Kebangsaan Malaysia, 2021)
Customer satisfaction is a vital component of service organisations that are significantly related to service quality. One of the electronic service quality that has to be prioritised, is website quality. Therefore, this study will determine the influence of electronic service quality and electronic word of mouth (eWOM) toward repurchase intention on e-commerce in Indonesia. Data were obtained from Google Form Online Questionnaires which were distributed through a short-link in WhatsApp, LINE, and Twitter applications during April 2019. This study applied the purposive sampling method where 458 qualified samples were matched to the specific criteria. Structural Equation Model (SEM) supported by LISREL software was used to analyse the data. The findings show that there are positive and significant influences of electronic service quality of pleasant and utilitarian dimensions to eWOM construction and repurchase intention. This research suggests managerial implication to e-commerce industry practitioners to reduce Tokopedia and also Instagram as the benchmark of electronic-based service quality. The managerial implication covers observing and adopting mobile application service quality aspects, service online review, and virtual communities. Besides, it is significantly suggested for future studies to explore more specific contexts of pleasant and utilitarian electronic service quality dimensions as in the B2B e-commerce, B2C e-commerce, and G2C e-commerce.